Control of psbA gene expression: in mature Spirodela chloroplasts light regulation of 32-kd protein synthesis is independent of transcript level - Fromm, Hillel (1985)
Spirodela oligorrhiza plants were used to study direct effects of light on plastid gene expression uncoupled from sequential chloroplast-developmental processes. Specific transcript levels were analysed using chloroplast, gene-fragment probes. Protein synthesis in vivo and in vitro was also measured. In tissue with mature chloroplasts, light/dark regimes had no substantial effect on transcript levels of the psbA gene coding for the 32-kd protein. However, under the same conditions, synthesis of the protein itself was dramatically affected. We conclude that in mature chloroplasts synthesis of 32-kd protein is regulated mainly at a translational level. Transcript levels of the rbcL gene, coding for the large subunit of ribulosebisphosphate carboxylase-oxygenase, were somewhat sensitive to light/dark effects, although not to the same degree as was synthesis of the protein. We conclude that translational events and transcript levels are involved in regulating synthesis of this polypeptide. Carbon deprivation in the dark reduced psbA and rbcL transcript levels appreciably below those found in non-starved, dark-grown tissue. This suggests that starvation and dark effects must be experimentally separated from each other for valid conclusions to be drawn about light/dark regulation of chloroplast gene expression.